Ayurvedic Management of Sandhivata W.S.R . To Osteoarthritis (International Journal of Environmental Sciences, 2025)
Sandhigata Vata is a disease seen commonly both in developing and developed countries. The disease causes mild, moderate or severe degree of morbidity and rarely mortality. The occurrence of problems is increasingly prevalent now a days due to change in lifestyle, food habits, social and cultural changes as well as travelling. It occurs when the protective cartilage that cushions the end of your bone wears down overtime. The common sign and symptoms of this disease is present in the form of Shoola, Shotha, Vatapoornadriti Sparsha and difficulty in flexion and extension of Sandhi. In Ayurveda osteoarthritis correlate to Sandhigata Vata. This paper deals with a case of Sandhigata Vata i.e., OA. After taking informed consent of the patient, he was given an Ayurvedic treatment for 30 days without any Allopathic medicine or any invasive technique. Patient was given Trayodashang guggulu, Tab Zonasto, Cap Stresscom, Cap. Mandukparni etc. There was a significant reduction noted in the symptoms . There were no clinically significant adverse reactions noted in the duration of treatment. The results of this study indicate the clinical efficacy of Ayurvedic treatment in the management of Sandhigata vata and patient gave highly satisfactory response after his treatment.